Foreign Policy of India as the Reflection of Change in its Ruling Elite - S. V. Velichkin (Международная аналитика, 2024)
The article examines the changes in the formulation, prioritisation and implementation of India’s foreign policy objectives as a result of a significant renewal of its political elite, triggered by the economic reforms that began in the 1990s. It is argued that India’s ruling elite is now largely identical to its political elite, whose mindset, although considerably younger and better educated, is more than ever defined by its self-identification with traditional values, which are religious and, for the vast Hindu majority, caste-based. At the same time, the composition of India’s elite has broadened during the reform years, mainly through the inclusion of middle and even lower castes in the traditional hierarchy. Many of its representatives tend to associate the strengthening of the country with a return to the “correct” cultural and civilisational basis which, in the centuries before foreign conquest, gave India what the y saw as its natural primacy in the world. The main change is the emergence of a sense of self-confidence among the elite, on which the so-called “new nationalism” of the “man of the people”, the current Prime Minister N. Modi, is based. Drawing on his statements, speeches by Foreign Secretary S. Jaishankar, and articles by Indian and Russian scholars, the author shows the innovations introduced by the Prime Minister in promoting India’s core national interests in a changing world. The article examines the creation of India’s own sphere of influence within the framework of the new Indo-Pacific strategy, the combination of cooperation and competition in relations with China, the reasons for the dynamic expansion of interaction with the United States and the “red lines” involved, the motives for developing a particularly privileged strategic partnership with Russia and for using multilateral formats, and the return to India’s agenda of the task of gaining the status of the main voice of the Global South. It is concluded that approaches to the imperative of building a multipolar world order “in which India would be a strong pole”, based on the priority goal of establishing for it the status of a great power and a global actor in world politics, create historic opportunities for increasing Russian-Indian interaction.